2004
DOI: 10.1017/s0001924000000385
|View full text |Cite
|
Sign up to set email alerts
|

Impact on composite structures

Abstract: The problem of impact damage in laminated composite structures, and the consequent reduction in residual strength, has been a topic of continual research for over two decades. The number of journal papers on the subject now runs into four figures and most have been conscientiously reviewed by Abrate(1991, 1994, 1998). This review is not intended to be in the academic tradition, with emphasis on acknowledging the authorship of all the various research initiatives. Instead we present our opinions so that the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
111
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(113 citation statements)
references
References 127 publications
(162 reference statements)
2
111
0
Order By: Relevance
“…In a sandwich construction, the core layer (reasonably thicker than the face sheets) made of same or different material constrained with the help of two stiff face sheets (upper and bottom). When the substantial deviation of the elastic properties between the sandwich layers (core and face sheet) exist, the sandwich structural component may encounter with delamination of the face sheet and the core layer, especially under impact loading [1]. Further, to reduce the unexpected delamination, a new concept called functionally graded material (FGM) is adopted in the design of the sandwich structures [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In a sandwich construction, the core layer (reasonably thicker than the face sheets) made of same or different material constrained with the help of two stiff face sheets (upper and bottom). When the substantial deviation of the elastic properties between the sandwich layers (core and face sheet) exist, the sandwich structural component may encounter with delamination of the face sheet and the core layer, especially under impact loading [1]. Further, to reduce the unexpected delamination, a new concept called functionally graded material (FGM) is adopted in the design of the sandwich structures [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Impact damage is a constant concern in the design of structures of composite materials, and frequently controls the allowable strains [1]. The largest effects are normally seen in compression, primarily due to the interaction of delaminations and local buckling.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practical engineering applications, composite structures seldom fail through a single delamination. More often, for example when thick composites are subjected to impact loading, multiple delaminations are generated, which is the result of complex damage formation and interactions between matrix cracks, fibre failures and delaminations [24][25][26]. It has been shown that embedded Z-pins interact with the composite material on a structural level [20,27], in that the embedded length of the pins relative to the crack plane has a direct influence on their suppression of delamination propagation.…”
Section: Introductionmentioning
confidence: 99%